Konflik Psikologis Tokoh dalam Novel Rindu Karya Tere Liye: Kajian Psikologi Sastra - Regi Ramadhani (Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
Research with title Psychological Conflict on Figures hearts Novel Rindu, by Tere Liye (Study Psychology Literature) ―is a research psychoanalyst kualitif research. Issues discussed in this research are: (1) How disposition possessed by the characters in the novel Rindu by Tere Liye ? (2). How is a form of psychological conflicts experienced by the characters in the novel Rindu work Tere Liye ? (3). What factors are causing psychological conflicts the characters in the novel Rindu by Tere Liye? This study is almed at knowing the characters in the novel Rindu by Tere liye. Methods used is research descriptive qualitative. Data sources of this study is novel Rindu the work of tere liye. Technique data analysis in this research was reduction data , presentation of data, and the withdrawal of conclusion. Dispositive figures gurutta having dispositive benevolent, likes to give advice, attention, a cleric famous, figures ambo uleng having dispositive a sailor bugis, not a quitter, sacrificing. Figures anna and elsa having dispositive plain as a child, figures daeng andipti having dispositive sacrificing. Figures Bonda upe you have a teacher quran reciting dispositive manner, Captain philips figure having the temper of a sailor great as well as benevolent. Father soerjaningrat having the nature of benevolent , sincere help , and happy teaching. The findingof this study are psychological conflict novel Rindu the work of tere liye thick with personality psychology. This novei containing psychology , especially personality which includes id , ego , and super ego. Of the three these aspects , ego the most comes up a lot or most owned by the leaders of . That personality appear because the figure having its own way to solve problems and made a choice well and wise. Personality each figures can control measures to be taken , choose segi-segi environment where he will give responses and decided insting-insting of those who will slaked and how to resolution .As gurutta figures, He has broad knowledge religion.By this he could help others in solve the problem.Kata-katanya that lemmbut wise and touched the heart and others that way it can be accepted.A figure gurutta always judge wisely.